INDUCTION OF IN VITRO TETRAPLOIDY IN Phalaenopsis violacea H.WITTE ORCHID BY COLCHICINE TREATMENT - Mushonev, Kameliah
Phalaenopsis violacea is an orchid from Sumatra and West Malaysia. This orchid population is declining in the recent years because of habitat decreasing, exposing P. violacea to the threat of extinction (vulnerable). To improve the conservation dan development of P. violacea orchids, various studies have been carried out, such as tissue culture method. This study aimed to determine the best media for protocorm like-body (PLB) proliferation and effective duration of immersion to induce tetraploidy of P. violacea PLB. In this study, PLBs were grown in half-strength Murashige & Skoog (½ MS) medium supplemented with various organic additives for 16 weeks, and subsequently immersed in 0.2% (w/v) colchicine for 6, 12, 24, 48 and 72 hours. After the immersion with colchicine, PLBs was planted in ½ MS medium containing 1% (w/v) sucrose and 0.1% (w/v) activated charcoal. After 6 weeks, PLBs was transfered into the proliferation media of P. violacea PLB for 40 weeks. Some aspects were observed in this study including survival rate and regeneration rate of PLBs, ploidy level of plantlets, stomata density, stomatal size, and number of chloroplasts in guard cell. The results showed that media supplemented with 5% (w/v) of Mas banana extract was the best medium for PLB proliferation by producing 1,2 ± 0,53 PLBs in 4 weeks, 2,80 ± 1,16 leaves in 12 weeks, and 0,50 ± 0,29 roots in 16 weeks. Immersion with 0.2% (w/v) colchicine solution for 72 hours is the most effective immersion duration, producing the most of tetraploidy in P. violacea PLBs. Flow cytometry result showed that 66.67% of the treated PLBs for 72 hours were tetraploid. If it involves its morphological characters, tetraploid have less leaves and roots than diploid. In addition, the stomatal size in tetraploid is bigger than diploid i.e. 43,27 ± 0,89 ?m, so that stomata density lower than about 26,33 ± 5,82/mm2 . The guard cell chloroplasts in tetraploid have more than diploid i.e. 76,33 ± 10,39 chloroplasts. From these results, it can be concluded that the media supplemented with 5% (w/v) of Mas banana extract become the best medium for PLB proliferation of P. violacea and 72-hours immersion is the most tetraploid induction plantlets.